Visualization of Alzheimer’s Disease Related α-/β-/γ-Secretase Ternary Complex by Bimolecular Fluorescence Complementation Based Fluorescence Resonance Energy Transfer - Wang, Xin; Pei, Gang (Frontiers in Molecular Neuroscience, 2018)
The competitive ectodomain shedding of amyloid-β precursor protein (APP) by α-secretase and β-secretase, and the subsequent regulated intramembrane proteolysis by γ-secretase are the key processes in amyloid-β peptides (Aβ generation. Previous studies indicate that secretases form binary complex and the interactions between secretases take part in substrates processing. However, whether α-, β- and γ-secretase could form ternary complex remains to be explored. Here, we adopted bimolecular fluorescence complementation in combination with fluorescence resonance energy transfer (BiFC-FRET) to visualize the formation of triple secretase complex. We show that the interaction between α-secretase ADAM10 and β-secretase BACE1 could be monitored by BiFC assay and the binding of APP to α-/β-secretase binary complex was revealed by BiFC-FRET. Further, we observed that γ-secretase interacts with α-/β-secretase binary complex, providing evidence that α-, β- and γ-secretase might form a ternary complex. Thus our study extends the interplay among Alzheimer’s disease related α-/β-/γ-secretase.